Model Pengelolaan Lingkungan Berbasis IP (Indeks Pencemaran) Berspektif CCME (Canadian Council of Ministers of The Environment) dan VED (Vital, Essential and Desirable) Dengan AHP Sebagai Perating (Studi Kasus : Kabupaten Gresik – Jawa Timur) - Irwanto Irwanto; Rony Prabowo (Institut Teknologi Adhi Tama Surabaya, 2023)
The quality of the environment in Gresik Regency has decreased along with the areas affected by pollution have increased. In 2021-2022 the areas affected by light industry pollution will increase by 18%, medium industry by 14%, and heavy industry by 15%. To find out how far the level of pollution is, a pollution index calculation for 7 rivers is carried out using the IP, CCME, VED and AHP methods as ratings. IP calculation results with water quality status lightly polluted 3 rivers (Mireng River 1.98, Lamong River 3.43 and Sukomulyo River 4.24), while 3 rivers (Afvour Wringinanom 7.02, Surabaya River 7.01 and Tengah River 8 .03) and the weight of 1 river (Solo River 10.57). CCME calculation results with poor water quality status 1 river (Tengah River 38.34) and 6 rivers with poor quality status (Afvour Wringinanom 44.66, Mireng River 58.5, Surabaya River 44.72, Solo River 49.34, Lamong River 52.91 and Sukomulyo River 48.12). The VED classification consists of 2 Vital Rivers (Solo River and Tengah River), Essential 3 Rivers (Afvour Wringinanom, Surabaya River, Lamong River) and Desirable 2 Rivers (Mireng River and Sukomulyo River). While the criteria and alternatives through the AHP rating there are 3 aspects namely technical and economic, health and environment, legal and institutional with 3 alternatives namely guidance, supervision and law enforcement, river conservation and the role of the community and business actors.